Species Differences in the Proportion of Plasma Lipoprotein Lipid Carried by High-Density Lipoproteins Influence the Distribution of Free and Liposomal Nystatin in Human, Dog, and Rat Plasma - Ramaswamy, Manisha (American Society for Microbiology, 1999)
The objective of this study was an interspecies comparison of free nystatin (NYS) and liposomal NYS (Nyotran) distribution in plasma. NYS and liposomal NYS at concentrations of 5, 10, and 20 μg of NYS/ml were incubated in human, dog, and rat plasma for 5, 60, and 180 min at 37°C. Following these incubations, plasma samples were separated into their high-density lipoprotein (HDL), triglyceride-rich lipoprotein, low-density lipoprotein, and lipoprotein-deficient plasma (LPDP) fractions by density-gradient ultracentrifugation, and each fraction was assayed for NYS by high-pressure liquid chromatography. Total plasma and lipoprotein cholesterol, triglyceride, and protein concentrations in each human, dog, or rat plasma sample were determined by enzymatic assays. When NYS and liposomal NYS were incubated in human, dog, or rat plasma, the majority of the NYS was recovered in the LPDP fraction. For the 5- and 60-min incubation times for all plasmas measured, a significantly greater percentage of NYS was recovered in the lipoprotein fraction (primarily HDL) following the incubation of liposomal NYS than following the incubation of NYS. There was a significant correlation between the lipoprotein lipid and protein profiles in human, dog, and rat plasmas and the distribution of NYS and liposomal NYS in plasma. In particular, differences in the proportion of plasma lipoprotein cholesterol, triglyceride, and apolar lipids (cholesteryl ester and triglycerides) carried by HDL influenced the distribution of NYS and liposomal NYS within plasmas of different species. These findings suggest that the distribution of NYS among plasma lipoproteins of different species is defined by the proportion of lipid carried by HDL, and this is possibly an important consideration when evaluating the pharmacokinetics, toxicities, and activities of these compounds following administration to different animal species.